Foliar Micromorphological Studies On Some Members Of The Family Fabaceae - DIPA CHAUHAN; M. DANIEL (International Journal of Pharma and Bio Sciences, 2011)
Twenty-nine plants belonging to the family of Fabaceae were investigated for their foliar trichome characters. Five plants were found glabrous, and the rest showed both glandular and non-glandular trichomes, which ranged from unicellular to multicellular structures. Three plants contained both glandular and non-glandular trichomes whereas four contained only the former and the rest non-glandular trichomes. These trichome characters being specific to the plants containing them are diagnostic features which can also be utilized as biomarkers to recognize the drug plants and to identify the plants in vegetative state.